Continuous hyperplastic models for overconsolidated clays - Einav, I; Puzrin, A; Houlsby, G (Elsevier, 2003)
This paper presents four constitutive models for prediction of the behaviour of overconsolidated clays under triaxial loading conditions. Their formulations are based on a new continuous hyperplastic framework. Continuous hyperplasticity allows the derivation of plasticity models which simulate smooth stress-strain behaviour, have continuous memory, and are guaranteed to obey the laws of thermodynamics. All four models are capable of simulating the triaxial stress-strain behaviour of overconsolidated clays in a wide strain range. The ability of the models to predict the stress path dependency of the clay behaviour is evaluated against experimental data obtained on undisturbed Laval samples of Bothkennar clay. © 2003 Elsevier Science Ltd. All rights reserved.